2006
DOI: 10.1186/bf03351923
|View full text |Cite
|
Sign up to set email alerts
|

GPS/Acoustic seafloor geodetic observation: method of data analysis and its application

Abstract: We have been developing a system for detecting seafloor crustal movement by combining kinematic GPS and acoustic ranging techniques. A linear inversion method is adopted to determine the position of seafloor stations from coordinates of a moving survey vessel and measured travel times of acoustic waves in seawater. The positioning accuracy is substantially improved by estimating the temporal variation of the acoustic velocity structure. We apply our method to the ranging data acquired at the seafloor reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(119 citation statements)
references
References 21 publications
2
117
0
Order By: Relevance
“…This point has been monitored since 2002 and was found to move landward by 8.5 cm/yr (Fujita et al, 2006). Sato et al (2011) reported its coseismic trenchward movement of ~24 m by the 2011 earthquake.…”
Section: Changes In Crustal Movements In 2011mentioning
confidence: 99%
“…This point has been monitored since 2002 and was found to move landward by 8.5 cm/yr (Fujita et al, 2006). Sato et al (2011) reported its coseismic trenchward movement of ~24 m by the 2011 earthquake.…”
Section: Changes In Crustal Movements In 2011mentioning
confidence: 99%
“…1). In addition, we use horizontal displacement data from three seafloor geodetic sites just above the source region, which were measured by the Japan Coast Guard using the GPS/acoustic measurement (Fujita et al, 2006). One of the seafloor sites off the Miyagi prefecture moved about 24 m in the ESE direction associated with the earthquake (Sato et al, 2011).…”
Section: Observationmentioning
confidence: 99%
“…We spent approximately 24 h performing an observation. More details on the analytical methodology are presented in Fujita et al (2006), Matsumoto et al (2008), Sato et al (2013a), and Watanabe et al (2014).…”
Section: Analytical Approachmentioning
confidence: 99%
“…In the early stages of our observations, we performed this inversion analysis constrained by the height of the grouped transponders over all epochs (e.g., Fujita et al 2006). The present analysis was constrained by the positional relationship of the grouped transponders for all epochs (e.g., Watanabe et al 2014).…”
Section: Analytical Approachmentioning
confidence: 99%